1999
DOI: 10.1038/sj.onc.1202859
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of the MYCN oncogene modulates MRP gene expression and response to cytotoxic drugs in neuroblastoma cells

Abstract: We have recently shown a close correlation between expression of the Multidrug Resistance-associated Protein (MRP) gene and the MYCN oncogene and provided evidence that high MRP expression is a powerful independent predictor of poor outcome in neuroblastoma (Norris et al., New Engl. J. Med., 334, 231 ± 238, 1996). The e ect of MYCN down-regulation on MRP expression and response to cytotoxic drugs was investigated in NBL-S neuroblastoma cells transfected wtih MYCN antisense RNA constructs. Concomitant with MYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 13 publications
3
47
0
Order By: Relevance
“…The clinical impact of these findings remains to be determined, since the prognostic value of P-gp expression in neuroblastoma is still a matter of debate. However, a close correlation between expression of the multidrug resistance-associated protein (MRP) gene and the MYCN oncogene as well as evidence for MRP expression as a powerful independent predictor of poor outcome in neuroblastoma has been shown before (Norris et al, 1996;Haber et al, 1999). The fact that resistance of SY5Y-TrkB cells to treatment with cisplatin, previously reported to be mdr1 independent (Fujiwara et al, 1990), was also enhanced, suggests that additional genes might be involved in mediating therapy resistance of TrkBexpressing neuroblastoma cells.…”
Section: Therapy Resistancementioning
confidence: 97%
“…The clinical impact of these findings remains to be determined, since the prognostic value of P-gp expression in neuroblastoma is still a matter of debate. However, a close correlation between expression of the multidrug resistance-associated protein (MRP) gene and the MYCN oncogene as well as evidence for MRP expression as a powerful independent predictor of poor outcome in neuroblastoma has been shown before (Norris et al, 1996;Haber et al, 1999). The fact that resistance of SY5Y-TrkB cells to treatment with cisplatin, previously reported to be mdr1 independent (Fujiwara et al, 1990), was also enhanced, suggests that additional genes might be involved in mediating therapy resistance of TrkBexpressing neuroblastoma cells.…”
Section: Therapy Resistancementioning
confidence: 97%
“…43 With respect to the MDR1/P-gp expression prognostic value, Haber's team indicated that very high MDR1 gene expression was associated with poor outcome in MYCN gene single-copy NB tumors. 44 The authors suggest that the MDR1 gene plays a clinical role in specific subgroups of primary untreated NB. Regarding MRP1, gene expression was first correlated with poor prognosis 43 and secondly with MYCN expression.…”
Section: Discussionmentioning
confidence: 99%
“…7 Established MYCN target genes include ornithine decarboxylase (ODC) 7,8 and multidrug resistance-associated protein 1 (MRP1). 9,10 ODC is the rate-limiting enzyme in the production of polyamines and its over-expression has been associated with a variety of malignancies. 11,12 MRP1 is a membrane-bound glycoprotein that confers resistance to many of the cytotoxic drugs used in the treatment of neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 MRP1 is a membrane-bound glycoprotein that confers resistance to many of the cytotoxic drugs used in the treatment of neuroblastoma. 13 We have previously shown a strong correlation between both MYCN and MRP1 expression, 10,[14][15][16] as well as MYCN and ODC gene expression. 17 Human neuroblastoma cell lines have been shown to consist of a mix of different cell types including neuroblastic (N-type) cells, substrate-adherent (S-type) cells and morphologically intermediate (I-type) stem cells that display a capacity for phenotypic interconversion between both N-type and S-type lineages.…”
Section: Introductionmentioning
confidence: 99%